Uporaba akustične resonance v meritvah in detekciji nivoja fluidov - Đonlagić, Denis (Informacije MIDEM, 1997)
A new level measurement and level detection methods are presented. They are based on the acoustic resonance of a waveguide and can be successfully implemented for fluid level measurements and fluid level detection in industrial plants, where problems of residues, deposits, foams, etc. can be expected. An experimetal level gauge and level detector have been built and tested under artificially induced residues, foams, deposits, etc. The resonance methods prove to be insensitive under extreme operating conditions. The proposed method represents and alternative to ultrasonic as well to some other level measurement and detection methods.
Keywords: akustični resonatorji; mehanika fluidov; merilna tehnika; merilne naprave; nivo fluidov